Social justice in «Calixto Garmendia»: an analysis from law and literature - Guabloche Gadea, Francis Dayana (2024)
«Calixto Garmendia», a work by Ciro Alegría, is about social inequality. The protagonist not only fights for the legal system of the country to function as it should, but also for society as a whole to operate with a minimum of equity, because it is evident that, in the Peru of this novel and in that of his time, inequality is overwhelming. What is portrayed is a clear injustice that is seen in Peru, and from there one can see realities of the past that have not changed and that still hurt humanity. On the other hand, the role of literature as a critical element to be able to think about justice and human rights today is discussed. And, finally, the importance of literary narratives is highlighted, as a means to understand the social and legal reality of justice, and thus achieve a more just society.